Prevalência de anemia em gestantes e sua associação com desfechos materno-fetais adversos - Dutra, Luanda Vasconcelos do Nascimento (2022)
In spite of being a common disease, the occurrence of anemia during pregnancy can have negative effects on maternal and child health, and may also be associated with increased fetal and maternal morbidity and mortality. This is a cross-sectional study, which aimed to identify the prevalence of anemia in pregnant women assisted by the a program called Family Health Strategy (in Portuguese: ESF), followed by a retrospective cohort that sought to associate its occurrence during pregnancy with adverse maternal-fetal outcomes: prematurity, low birth weight and low fetal vitality. The sample consisted of 400 pregnant women residing in the municipality of Cruz-CE. They were monitored by the ESF between 2019 and 2020. Data were obtained by reviewing their electronic medical records, the Municipal Laboratory database and SINASC (a Brazilian Information System on Live Births). Were considered anemic only the pregnant women with Hb values <11.0 g/dL and/or Ht<33%. Data analysis were done by calculating the Prevalence Ratio (PR), and the qualitative (categorical) variables were evaluated using univariate tables, with absolute and relative frequencies. Moreover, in the analytical part, the variables were analyzed using Pearson's Chi-square test and/or Fisher's exact test. Additionally, Normality Tests (Histogram and Shapiro-Wilk) were performed, and then Student's T and Kruskal-Wallis tests were adopted, with a significance level (α) of 5%. Hematimetric parameters were subdivided into: Hb < 10g/dL; Ht < 33%; Hb < 11g/dL and Ht < 33%; and MCV value < 80fL, in order to obtain greater specificity in potential risks. The prevalence of gestational anemia found was 25.2% (101 cases), classifying it as a moderate public health problem. Also there was a significant association between this pathology and younger maternal ages. When the Hb < 10g/dL; Ht < 33% and Hb <11g/dL and Ht < 33%, maternal anemia was significantly associated with low Apgar scores in newborns at the 1st but also at the 5th minute. The study aimed to provide a view of the severity of the prevalence of gestational anemia, as well as the main factors that might be associated with adverse events in pregnancy/childbirth, in order to contribute to the planning of actions and strategies aimed at maternal and child health.